Fomulation And Physical Quality Testing Of A Scrub Gel With Ethanol (70%) Extract Of Pineapple Core (Ananas comosus (L.) Merr.) - Rizka Nursilah Ode; Juvita Herdianty; Sri Rahayu Dwi P.; Arif Wijayanto (Strada Journal of Pharmacy, 2024)
Scrubs are widely used in cosmetic care, primarily for exfoliation to remove dead skin cells. This study used a 70% ethanol extract from pineapple cores (Ananas comosus (L.) Merr.), which contains active compounds such as bromelain, flavonoids, and saponins. These compounds were formulated into a scrub gel that potentially benefits skin health, especially in exfoliation. The aim of this study was to evaluate good physical quality characteristics, including organoleptic properties, homogeneity, pH, viscosity, adhesion, and spreadability, based on varying concentrations of ethanol extract from pineapple cores. This research employed a true experimental method with a post-test only design to determine the best physical quality of scrub gel formulations containing pineapple core extract (Ananas comosus (L.) Merr.) at three extract concentrations: 3%, 5%, and 10%. The physical quality evaluation of the scrub gel, including organoleptic properties, homogeneity, viscosity, adhesion, and spreadability, showed good results and met the standards. However, the pH testing results for the three formulations did not meet the standards, as they were relatively neutral to slightly acidic (6.48-7.58). The hedonic test results indicated that Formulation 2 (5%) received the highest ratings in terms of aroma and texture, while Formulation 1 (3%) and Formulation 3 (10%) also showed a tendency to be preferred in certain aspects, particularly in terms of color and texture. The Kruskal-Wallis test followed by the Mann-Whitney test showed significant differences in pH, viscosity, and adhesion (p-value: 0.46-0.05 ≤ 0.05). Meanwhile, the One-Way ANOVA test on spreadability showed a very significant difference in spreadability, with Formulation 3 and the negative control having the highest spreadability (p-value <0.005). The concentration of pineapple core extract affects the physical and sensory characteristics of the scrub gel, with the addition of active pineapple core extract at a concentration starting from 3% already showing good physical characteristics.